John Puller : No Man's Land - Book 4 - Baldacci, David (New York : Grand Central Publishing, 2016)
John Puller may be the US Army's most tenacious investigator, but he is not equipped to face the truth about his mother's disappearance thirty years ago. New evidence has come to light suggesting that Puller's father -- a highly decorated army veteran -- may have murdered his wife. When Puller's friend, intelligence operative Veronica Knox, arrived on the scene, he realized that there is far more to this case than he first though. He knows that nothing will prevent him from discovering what really happened to his mother -- even proving that his father is a killer. Meanwhile, Paul Rogers has just been paroled after spending ten years in a high-security prison for murder. And with his freedom comes a desire to pay back old debts. Harbouring a dark past that changed him in unimaginable ways, Rogers embarks on a journey across the country, set on a path of revenge against the people who took away his humanity. As both men uncover a trail of deception that stretches back decades, they realize that the truth will bind them together in ways they could never have imagined. --
Keywords: United States -- Army Criminal Investigation Command -- Fiction; Cold cases (Criminal investigation) -- Fiction; Murder -- Fiction -- Investigation; Parolees -- Fiction; Detective and mystery fiction